KEANEKARAGAMAN JENIS BURUNG DIURNAL DI HUTAN JAJAU KECAMATAN MENTEBAH KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Suhendra, Try; Erianto, Erianto; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2020)
Mentabah sub-district is one of the territories in  Kapuas Hulu, the province of  West Borneo. The width is about  781,26 km²  with enormous potential for biodiversity. One of them is Jajau forest. The local people called it Jajau Forest that also known as Kerangas forest. The purpose of this research is to collect data about the diversity of Diurnal species in Jajau Forest in Mentabah sub-district, Kapuas Hulu, the province of West borneo. IPA ((Index Point Abundance) is used in this research that placed purposively. The result of this research shows that there are 111 birds species could be indetified with 938 birds include 39 families. This research showh that the variety of birds in this are is so high, it is 4.4221.Keywords: diversity of birds, Jajau Forest, Mentebah District